Perancangan Antarmuka Pengguna Sistem Informasi Pengelolaan Nilai Siswa SMAIT Ibnu Abbas menggunakan Metode Human Centered Design - Fathiya Ihsani; Hanifah Muslimah Az-Zahra; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Score management is something that is routinely done in educational institution that give the result in the form of report cards. Score management in SMAIT Ibnu Abbas still uses Microsoft Excel and teachers feel ineffective. Based on interview with teachers and homeroom teachers, SMAIT Ibnu Abbas requires a student management information system as information for student guardians, streamlining report cards distribution, and storing report cards. This study aims to make it easier for teachers to manage grades so that they can run effectively, simplify the distribution, and make it easier for students' guardians to access the report cards. The Human Centered Design method focuses on humans in the design process and has 4 stages, those are; determine the context of use, determine usage requirements, create design solutions, and evaluate design results. This research produces a prototype of an information system based on a website application. The stage of determining the context of use is determined by 5 system users, those are admin, subject teachers, homeroom teachers, students, and student guardians. Determination of tasks and goals for users, along with the system environment. The stage of determining user requirements produces some features, 43 functional requirements, and 1 non-functional requirement. The design solution stage resulted 31 wireframe page views, suggestions for improvement, and a final design prototype of 45 pages. The stage of evaluating the results of the design was tested using the System Usability Scale (SUS) to 13 respondents consisting of all user groups. The test results show an average of 70,769 which indicates that the design is acceptable. The results of usability testing on the effectiveness aspect showed the results of 98.75%.